The Ecology of Disturbance Interactions. (16th September 2020) - Burton, Philip J; Jentsch, Anke; Walker, Lawrence R
Abstract: Global change has been accompanied by recent increases in the frequency and intensity of various ecological disturbances (e.g., fires, floods, cyclones), both natural and anthropogenic in origin. Because these disturbances often interact, their cumulative and synergistic effects can result in unforeseen consequences, such as insect outbreaks, crop failure, and progressive ecosystem degradation. We consider the roles of biological legacies, thresholds, and lag effects responsible for the distinctive impacts of interacting disturbances. We propose a hierarchical classification that distinguishes the patterns and implications associated with random co-occurrences, individual links, and multiple links among disturbances that cascade in chains or networks. Disturbance-promoting interactions apparently prevail over disturbance-inhibiting ones. Complex and exogenous disturbance cascades are less predictable than simple and endogenous links because of their dependency on adjacent or synchronous events. These distinctions help define regional disturbance regimes and can have implications for natural selection, risk assessment, and options for management intervention.